The burden of history(?): Remembering the Holocaust and Attitudes toward Asylum Seekers in Israel - Ariely, Gal (International journal of conflict and violence, 2018)
Two connected studies examine how universalist and particularist views of the Holocaust influence Israeli Jews’ attitudes toward asylum seekers. Study 1 (N = 500) investigated the degree to which universalist and particularist perceptions of the “lessons” of the Holocaust correlate with exclusionist views toward asylum seekers. It was found that a universalist perception of the “lessons” of the Holocaust was negatively related to exclusionist attitudes, and a particularist perception positively related to exclusionist attitudes—even after controlling for religiosity and political affiliation. Study 2 comprised three survey experiments (N = 298, 280, and 320, respectively) investigating whether presentation of universalist versus particularist texts about the Holocaust would impact exclusionist attitudes. It was found that exposure to a universalist text reduced negative attitudes toward asylum seekers and increased support for treating wounded Syrians in Israeli hospitals. Exposure to a particularist did not increase exclusionist attitudes